The impact of increasing multitarget stool DNA use among colorectal cancer screeners in a self-insured US employer population - Joanne M Hathway; Lesley-Ann Miller-Wilson; Abhishek Sharma; Ivar S Jensen; Weiyu Yao; Sajjad Raza; Philip D Parks; Milton C Weinstein (Journal of Market Access & Health Policy, 2021)
Background: In the United States (US), colorectal cancer (CRC) is the second leading cause of cancer-related deaths. With the majority of the US population covered by employer-based health plans, employers can play a critical role in increasing CRC screening adherence, which may help avert CRC-related deaths. Therefore, it is important for self-insured employers to consider the impact of appropriate utilization of CRC screening options. Objective: To evaluate the impact of increasing multitarget stool DNA [mt-sDNA (Cologuard®)] use among CRC screeners from the perspective of a US self-insured employer. Methods:A 5-year Markov model was developed to quantify the budget impact of increasing mt-sDNA from 6% to 15% among average-risk screeners using colonoscopy, fecal immunological test, and mt-sDNA. Data on direct medical costs were obtained from published literature, Medicare CPT codes, and the Healthcare cost and Utilization project. Indirect costs included productivity loss due to workplace absenteeism for CRC screening and treatment. Results: With a hypothetical population of 100,000 employees with screeners aged 50–64 years, compared to status quo, increased mt-sDNA utilization resulted in no differences in the numbers of cancers detected and the overall direct and indirect cost savings were ~$214,000 ($0.04 per-employee-per-month) over 5 years. Most of the savings were due to a reduction in the direct medical expenditure related to CRC screening, adverse events, and productivity loss due to colonoscopy screening. Similar results were observed in the model simulation among screeners aged 45–64 years. Conclusion: Increased utilization of mt-sDNA for CRC screening averts direct and indirect medical costs from a self-insured US employer perspective.